Implementasi Kepemimpinan Kepala Madrasah terhadap Peningkatan Profesionalisme Guru di MIN 2 Kota Sawahlunto - Elizasri Elizasri; Suswati Hendriani (Journal on Education, 2023)
This article aims to determine the implementation of the Madrasah head's leadership towards increasing teacher professionalism at MIN 2 Sawahlunto City. This research uses a qualitative approach with a literature review method. The data collection technique used is by examining or exploring several journals, books, and documents (printed or electronic) as well as other data sources that are considered relevant to this article. The findings of this article are based on eight principal leadership principles that can be applied to develop their madrasah. The principles in question consist of constructive, creative, participatory, cooperative, delegative, integrative, rational, pragmatic, exemplary, and adaptable and flexible. Where the madrasa head is responsible for fostering and forming professional teachers in order to build quality madrasas. Therefore, the leadership of the Madrasa head and teacher professionalism are two factors that influence each other.